Aspectos clínicos, histológicos e de microscopia eletrônica dos granulomas de intubação das pregas vocais - Martins, Regina Helena Garcia [UNESP]; Dias, Norimar Hernandes [UNESP]; Dos Santos, Daniela Carvalho [UNESP]; Fabro, Alexandre Todorovic [UNESP]; Braz, José Reinaldo Cerqueira [UNESP] (Elsevier, 2009)
Granulomas are bilateral and pediculated lesions of the vocal apophysis. Etiologies: intubation, reflux, trauma, vocal abuse, idiopathic origin. Aim: To analyze the clinical and morphological aspects of post intubation granulomas. Methods: retrospective study of patients submitted to microsurgery for post intubation laryngeal granulomas seen at our Medical School starting in 2002. We analyzed: age, gender, indication and time of intubation, symptoms, videolaryngoscopic diagnosis and biopsy findings. Light microscopy was performed on all specimens, and electron microscopy on three of them. Results: ten patients (7 females and 3 males), between the ages of 2 and 72 years, intubation time between 4h and 21 days. Hoarseness was a frequent symptom, starting in the first week following extubation. Histology shows mild epithelial hyperplasia, severe inflammation and vessel proliferation in the corion. Under SEM, the epithelium presented mild superficial desquamation. Under TEM, intracellular junctions showed widening with structural changes in the desmosomes. In the corion there were vessel proliferations, inflammation and fibroblasts with structural alterations. Conclusions: post intubation granulomas appear in any age and hoarseness is a frequent symptom. Morphological alterations occur in the corion as vessel proliferations, inflammation, and intracytoplasmatic alterations in fibroblasts suggesting cellular dysfunction and damage. © Revista Brasileira de Otorrinolaringologia.
Clinical, histological and electron microscopic aspects of vocal fold granulomas
Keywords: Granuloma; Intubation; Larynx; Morphology